CRIMINAL POLICY ON INDONESIAN POLICE RESTORATIVE JUSTICE IMPLEMENTATION PERIOD 2021-2023 - Nugroho, Sofyan; Pujiyono, Pujiyono; Supeno, Bambang Joyo (Universitas 17 Agustus 1945 Semarang, 2024)
Criminal policy or criminal politics as an effort to prevent and control crime is essentially an integral part of efforts to protect society (social defense) and efforts to achieve social welfare, both of which are an integral part of social politics (social policy). This is related to the criminal justice system is carried out by the police as the front guard in maintaining security and social order in society and law enforcement. Legal reform carried out by the Police through Restorative Justice is a new instrument in realizing social justice. Therefore, the first formulation of the problem in this paper is a) What is the regulatory framework of Indonesian Police Restorative Justice in Indonesia? b) How is the implementation of Indonesian Police Policy of Restorative Justice in Indonesia period 2021 – 2023? Methodologically, this research uses a qualitative approach, with a qualitative research design and literature study. The research results show a number of findings: First, there are still very few cases that use alternative dispute resolution for criminal acts. Second, the importance of a legal and regulatory policy framework that is based on restorative justice that is fair and has legal certainty.